STUDY ON THE IMPORTANCE OF TEHNICAL EXERCISES ON THE SPECIFICS OF THE PLAYING POSITION - ATTACKERS - Cătălin-Andrei Tatarcan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Following the application of the technical exercises, as well as the test specific of the football game detailed below, with emphasis on the specific actions of the players in the game, we noticed an improvement in terms of technique on the specifics of the position (attacker). They developed their specific skills for the attackers. Technical elements and procedures for driving and hitting the ball specific to the attacking players were used, actions carried out outside the penalty area (square). The study was conducted on a group of children from the club Luceafărul Bucovina Suceava.